A Scoping Review of Magnetic Resonance Modalities Used in Detection of Persistent Postconcussion Symptoms in Pediatric Populations. (February 2023) - Sheldrake, Elena; Lam, Brendan; Al-Hakeem, Hiba; Wheeler, Anne L.; Goldstein, Benjamin I.; Dunkley, Benjamin T.; Ameis, Stephanie; Reed, Nick; Scratch, Shannon E.
Up to 30% of youth with concussion experience PPCSs (PPCS) lasting 4 weeks or longer, and can significantly impact quality of life. Magnetic resonance imaging (MRI) has the potential to increase understanding of causal mechanisms underlying PPCS. However, there are no clear modalities to assist in detecting PPCS. This scoping review aims to synthesize findings on utilization of MRI among children and youth with PPCS, and summarize progress and limitations. Thirty-six studies were included from 4907 identified papers. Many studies used multiple modalities, including (1) structural (n = 27) such as T1-weighted imaging, diffusion weighted imaging, and susceptibility weighted imaging; and (2) functional (n = 23) such as functional MRI and perfusion-weighted imaging. Findings were heterogeneous among modalities and regions of interest, which warrants future reviews that report on the patterns and potential advancements in the field. Consideration of modalities that target PPCS prediction and sensitive modalities that can supplement a biopsychosocial approach to PPCS would benefit future research.